Terrestrial and aquatic responses to climate change and human impact on the southeastern Tibetan Plateau during the past two centuries - Wischnewski, J; Kramer, A; Kong, ZC; Mackay, AW; Simpson, GL; Mischke, S; Herzschuh, U (WILEY-BLACKWELL, 2011)
Rapid population growth and economic development have led to increased anthropogenic pressures on the Tibetan Plateau, causing significant land cover changes with potentially severe ecological consequences. To assess whether or not these pressures are also affecting the remote montane-boreal lakes on the SE Tibetan Plateau, fossil pollen and diatom data from two lakes were synthesized. The interplay of aquatic and terrestrial ecosystem response was explored in respect to climate variability and human activity over the past 200 years. Nonmetric multidimensional scaling and Procrustes rotation analysis were undertaken to determine whether pollen and diatom responses in each lake were similar and synchronous. Detrended canonical correspondence analysis was used to develop quantitative estimates of compositional species turnover. Despite instrumental evidence of significant climatic warming on the southeastern Plateau, the pollen and diatom records indicate very stable species composition throughout their profiles and show only very subtle responses to environmental changes over the past 200 years. The compositional species turnover (0.36-0.94 SD) is relatively low in comparison to the species reorganizations known from the periods during the mid-and early-Holocene (0.64-1.61 SD) on the SE Plateau, and also in comparison to turnover rates of sediment records from climate-sensitive regions in the circum arctic. Our results indicate that climatically induced ecological thresholds are not yet crossed, but that human activity has an increasing influence, particularly on the terrestrial ecosystem in our study area. Synergistic processes of post-Little Ice Age warming, 20th century climate warming and extensive reforestations since the 19th century have initiated a change from natural oak-pine forests to seminatural, likely less resilient pine-oak forests. Further warming and anthropogenic disturbances would possibly exceed the ecological threshold of these ecosystems and lead to severe ecological consequences.